Comparison of external genetic of Wareng and Kampung Chicken, observed from introgression rate and genetic variability - T Sartika; D.K Wati; H.S Iman Rahayu; S Iskandar (Indonesian Center for Animal Research and Development (ICARD), 2008)
Wareng and Kampung chicken are Indonesian native chicken that have good potential to be dual purpose chicken. Information on these chickens has not hast’n widely published so that their genetic potential is unknown. The purpose of this research is to collect basic data of the external genetic characteristic from Wareng and Kampung chickens consisting feather color, feather pattern, feather feature, feather shine, shank color and comb shape; to identify rate of introgression imported breed (Rhode Island Red, White Leghorn and Barred Plymouth Rock), the purity and genetic variability of Wareng and Kampung chickens. This study was carried out at the Research Institute for Animal Production, Ciawi, Bogor. Materials used were 361 of Wareng chickens (313 females, 48 males) and 439 of Kampung chickens (352 females, 87 males). Data were analyzed using formulas to identify gene frequency, rate of introgression of purity native gene frequency and the genetic variability. The result showed that the control of gene constitution on external characteristic of Wareng chicken was I_ E_ bb S_ Id_ pp and ii e+ _bb ss idid pp on Kampung chicken. Wareng chicken own constitution of gene the same as with White Leghorn (II EE SS BB IdId pp). Wareng Chicken is not containing frequency of original gene of Indonesian local chicken (Kampung). The level of influence value (rate of introgression) from Europe and American chicken for Wareng chicken was of equal to 84% and 25% to Kampung chicken. So that the purity for Wareng chicken was 16% and 75% was for Kampung chicken. The variability genetic of Kampung chickens (39%) higher than Wareng chicken (16%). Key Words: Wareng Chicken, Kampung Chicken, External Genetic, Introgression Rate